Political sophistication in Central and Eastern Europe: How can parties help?. (May 2015) - Popa, Sebastian Adrian
This article investigates how parties can influence the level of political sophistication their supporters have. Although the importance of parties in providing their supporters with political information was first suggested in early studies of voting behaviour, this level of analysis has been omitted from individual studies of political sophistication. Focusing on the political environment of post-communist societies, where parties played a key role in helping citizens understand politics, I theorize both a direct and an indirect path through which parties can contribute to the level of sophistication of their supporters. Using cross-national data from the Eurequal 2007 project on 13 post-communist countries, I show three characteristics related to parties' motivation to mobilize the electorate against the status quo that have an impact on individual level political sophistication. Results from a multi-level model suggest that supporting a non-incumbent, smaller or right-wing party is related, either directly or in interaction with individual characteristics, to higher levels of political sophistication. These findings shed light on how looking at political parties can help us better understand the differences in the levels of political sophistication among citizens.